Evaluation of photon-counting micro-CT scanning for imaging marine organisms - Xue, Mengjia; Xie, Tianwu; Liu, Qian (Frontiers in Marine Science, 2025)
IntroductionAnatomical information is crucial in marine biology research. Traditionally, destructive techniques, such as slice imaging of the sample, are used to image the inside of the sample, which are unsuitable for valuable or rare specimens. While energy-integrating detectors computed tomography (CT) can provide non-invasive anatomical information, it suffers from limitations such as low spatial resolution, high noise, and an inability to analyze material composition.MethodsPhoton-counting (PC) micro-CT offers a promising alternative, enabling noninvasive imaging of both internal and external structures of marine organisms. Various species, including bivalves, conchs, and fish otoliths, were scanned using this advanced technology. The influence of different tube voltages on image quality is analyzed in this paper.ResultsOne of the key capabilities of PC micro-CT is the reconstruction of virtual monoenergetic images and material decomposition, which has been tested. To further enhance soft tissue visualization, iodixanol solution was employed for contrast imaging.DiscussionPC micro-CT provides high resolution both in non-contrast images and iodixanol-contrast images which digestive tracts and glands can be seen. Material decomposition of fish otoliths revealed the characteristic wheel-shaped distribution of calcium content. PC micro-CT has the potential ability for imaging marine organisms and promising future in broader utilization in marine biological research.